Life-Cycle Assessment Of Compressed Bricks Using Cameron Highlands Reservoir Sediment As Primary Material: Recipe Method - Tan, Jia Hui (2021)
Disposal of dredged sediments has recently been linked to a multitude of environmental and health issues, rather than bringing any economic value to the country. Furthermore, the overexploitation of clay for brick production is destructive to the environment. Hence, it is essential to develop a decisive method to minimize the land and water pollution resulting from improper disposal as well as lessening the consumption of natural resources in the brick production. The key objective of this study is to identify environmental impacts of compressed bricks using Cameron Highlands reservoir sediment as primary material. OpenLCA software is used to evaluate the environmental impact of one kilogram of compressed sediment brick and compressed clay brick by using allocation of Ecoinvent. The life cycle assessment is conducted in a cradle-togate manner. The production process and brick mixtures are based on a recent study conducted in Malaysia. This study also presents the avoided process of recycled sediments in the life cycle assessment. Moreover, the ReCiPe Midpoint approach analyses the environmental impacts categories such as climate change, human toxicity and freshwater ecotoxicity, whereas the damage categories are quantified in terms of human health, ecosystem and resource availability by using ReCiPe Endpoint indicator. According to the results of the LCA, compressed sediment brick with a mix proportion of 70 % sediment silt, 20 % sediment sand and 10 % cement is favourable from an environmental perspective. In comparison to compressed clay brick, the compressed sediment brick offers promising options for the long-term because it contributes high environmental performance among all the impact and damage categories assessed in this study. A review of engineering properties and cost for various types of bricks are also involved in this study. Overall, the compressed sediment brick is a cost-effective solution because it has been proven to generate lesser environmental impact and cost without compromising engineering properties.